2019
DOI: 10.1038/s41598-019-54468-5
|View full text |Cite
|
Sign up to set email alerts
|

Long range infrasound monitoring of Etna volcano

Abstract: Among ground-based volcano monitoring techniques, infrasound is the only one capable of detecting explosive eruptions from distances of thousands of kilometers. We show how infrasound array analysis, using acoustic amplitude and detection persistency, allows automatic, near-real-time identification of eruptions of Etna volcano (Italy), for stations at distances greater than 500 km. A semi-empirical attenuation relation is applied to recover the pressure time history at the source using infrasound recorded at g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…In particular, it was demonstrated that infrasound can play a key role in supporting early warning systems by notifying in near real-time the onset of explosive eruptions, thus reducing the risk of aircrafts encountering volcanic ash in poorly monitored regions. Applying the procedure described by Marchetti et al [32] , the amplitude of infrasound detections associated with the July and August eruptions are…”
Section: Long-range Propagation Modelling For the July And August Ermentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it was demonstrated that infrasound can play a key role in supporting early warning systems by notifying in near real-time the onset of explosive eruptions, thus reducing the risk of aircrafts encountering volcanic ash in poorly monitored regions. Applying the procedure described by Marchetti et al [32] , the amplitude of infrasound detections associated with the July and August eruptions are…”
Section: Long-range Propagation Modelling For the July And August Ermentioning
confidence: 99%
“…The source amplitude is then multiplied by the normalized number of detections per minute, which reflects the time persistency of the signals recorded at the array. The derived infrasound parameter (IP) is used to define the occurrence of significant explosive volcanic activity when a fixed threshold of 60 is exceeded [32] . Figure 6 shows the IP variations at stations AMT, IS48, OHP, and IS26, color-coded according to the alert level.…”
Section: /17mentioning
confidence: 99%
“…Many volcanoes are monitored by observatories that try to estimate at least the probability of the different hazardous volcanic events [3]. Different time series can be monitored and hopefully used for forecasting, including seismic data [4], geomagnetic and electromagnetic data [5], geochemical data [6], deformation data [7], infrasonic data [8], gas data [9], thermal data from satellite [10] and from the ground [11]. Whenever possible, a multiparametric approach is always advisable.…”
Section: Introductionmentioning
confidence: 99%
“…The pioneer works are Passechnik (1959) at the Bezymyanny volcano (Kamchatka, Russia) and Goerke et al (1965) at the Agung volcano (Bali, Indonesia). In recent years, highperformance infrasound stations are operated as a part of the International Monitoring System (IMS) for verification of the Comprehensive Nuclear-Test-Ban Treaty (CTBT) and are also used for monitoring and studying volcanic eruptions (Evers and Haak 2005;Le Pichon et al 2010;Matoza et al 2017;Marchetti et al 2019).…”
Section: Introductionmentioning
confidence: 99%